2017
DOI: 10.1016/j.jjcc.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Increased C-reactive protein plasma levels are not involved in the onset of post-operative atrial fibrillation

Abstract: These results suggest that increased CRP plasma levels that are not associated with an inflammatory process are not sufficient to trigger AF after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…Whole inflammatory cascade, including IL-6, must be prompted to induce AF. Additionally, a recent study concluded that higher CRP levels might be associated with gene polymorphisms rather than increased inflammation [Del Campo 2017]. Since we included patients with recent acute coronary syndrome, CRP levels might be higher compared to other studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Whole inflammatory cascade, including IL-6, must be prompted to induce AF. Additionally, a recent study concluded that higher CRP levels might be associated with gene polymorphisms rather than increased inflammation [Del Campo 2017]. Since we included patients with recent acute coronary syndrome, CRP levels might be higher compared to other studies.…”
Section: Discussionmentioning
confidence: 90%
“…Inflammation has a substantial role in atrial fibrillation as many studies obviously demonstrated the link [Harada 2015]. CRP as a marker of inflammation seems questionable due to controversial findings of different studies [Erdem 2014;Del Campo 2017]. CRP is not a reliable marker since affected by numerous factors.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for Af are diverse and include advancing age, male gender, diabetes mellitus, cardiovascular disease, post-cardiac surgery, some biomarkers, genetics, etc. [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, implementing preventive measures against postoperative lung infections, such as continuous low-ow oxygen inhalation, may reduce POAF. However, this assertion has taken issue with some scholars [23] . In our study, we found pulmonary infection was the most frequent postoperative complication, accounting for 72.2% (70/97) of all cases, and it was signi cantly associated with the development of POAF (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%